MEMAKNAI DIRI MELALUI KEPEKAAN SENI DAN KHAOS : Sebuah Tinjauan Seni sebagai Manifestasi Satu Perjalanan Jiwa - Dyah Gayatri Puspitasari (Jurnal Dimensi Seni Rupa dan Desain, 2015)
AbstractThe chaotic of modernity has changed the world into a wilderness of materialculture representation. Life is conveyed by the superficial and shallowexperience, which gives a sensation or even dogmatic that inspire the perceptionof reality fastly, including the self-reality. The art sensibility and 'chaos' are thepower of life that creates human self-relation with essence of life. The possibilityof looking beyond and bring ourselves to being beyond. Meaning fulness reallyrelies on human's aesthetical perspective, which sees the world as non-materialworld; the existence of 'Being' that has become the meaning of all materialsurface. Art has undoubtedly become the conductor of self-unity. Through thephenomenology of Husserl and the aesthetic of Deleuze, the contiguity ofselfness with art is interpreted as the chaotic exploration, the unity of subjectobjectexploration on the pre-reflective, pre-theoritical level. Art is a sensation ofchaotic embodiment, and art sensibility is the nature of chaotic power. Fromthis, the aesthetical selfness is originated, a selfness that could enter themeditation zone with a sensibility and intellegency up to the level of consciousreflectivity, which will be able to touch the depth of human's spiritual zone. AbstrakHirukpikuk modernitas kian mengubah dunia menjadi belantararepresentasi budaya material. Kehidupan terhantar pada pengalamanyang bersifat permukaan, dangkal, hingga memberi sensasi bahkandogmatis yang begitu cepat pengaruhi persepsi akan realitas, termasukrealitas diri. Kepekaan seni dan 'khaos' merupakan daya hidup penciptahubungan diri manusia dengan esensi kehidupan. Memungkinkansuatu looking beyond dan membawa diri pada being beyond.Kebermaknaan sedemikian bergantung pada cara pandang estetikmanusia akan dunia sebagai dunia non material, keberadaan suatu'Ada' (Being), yang menjadi makna dari segala kematerialan yangmengemuka. Seni menjadi keniscayaan penghantar keterleburan diri kedalamnya. Melalui fenomenologi Husserl dan estetika Deleuze,persentuhan diri dengan seni termaknai sebagai petualangan khaos,petualangan keterleburan Subyek-Obyek pada tingkat pra-reflektif,pra-teoritis. Seni adalah sensasi pengejawantahan khaos, dan kepekaanseni perihal menangkap kekuatan khaos. Dengannya terlahir sosok 'diriyang estetik', diri yang termampukan memasuki wilayah perenungandengan suatu kepekaan dan kecerdasan hingga pada tingkatreflektivitas kesadaran yang mampu menyentuh wilayah spiritualkedalaman makna manusiawinya.